# factoring : (x+1)^3+(x-1)^3 nd also (3x-7)²-2(x+1)(3x-7)+(x+1)²?

hello guys i may need some of your answers! could you do this for me with steps please :( ?

### 3 Answers

- mr. coolLv 57 years agoBest Answer
(x+1)^3 + (x-1)^3

(x^2+2x+1)(x+1) + (x^2-2x+1)(x-1)

x^3 + 2x^2 + x + x^2 + 2x + 1 + x^3 - 2x^2 + x - x^2 + 2x - 1

x^3 + x^3 + 2x^2 - 2x^2 + x^2 - x^2 + x + 2x + x + 2x + 1 - 1

2x^3 + 6x

2x(x^2 + 3)

(3x-7)^2 - 2(x+1)(2x-7) + (x+1)^2

(3x-7)(3x-7) + (-2x-2)(2x-7) + (x+1)(x+1)

9x^2 - 42x + 49 - 4x^2 + 10x + 14 + x^2 + 2x + 1

(9x^2 - 4x^2 + x^2) + (-42x + 10x + 2x) + (49 + 14 + 1)

6x^2 - 30x + 64

2(3x^2 - 15x + 32)

- costinLv 43 years ago
i'm rotten at math, too, Francesca. I used to instruct fourth grade, and not too many fourth graders do plenty algebra. even however, my son is extremely reliable in math, so I asked him the thank you to try this: 4 (2x-5)=13-(x-3) 8 x 20 = 13-x +3 8x -20 = -x + sixteen 9x=36 x=4 (x+4) (x-4)= 9 x (squared) +4x-4x-sixteen=9 x (squared)-sixteen=9 x= +or-5 x (x+a million) = (x-7) (x-6) x (squared) +x =x (squared) -13x + 40 two +13 x 14x = 40 two x =3 wish this enables.